GMAT Question of the Day: Daily via email | Daily via Instagram New to GMAT Club? Watch this Video

 It is currently 04 Aug 2020, 04:07

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If m^(-1) = -1/3 then m^(-2) is equal to

Author Message
TAGS:

### Hide Tags

Manager
Joined: 02 Dec 2012
Posts: 172
If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

20 Dec 2012, 06:23
5
1
23
00:00

Difficulty:

5% (low)

Question Stats:

85% (00:37) correct 15% (00:51) wrong based on 2015 sessions

### HideShow timer Statistics

If $$m^{(-1)} = -\frac{1}{3}$$ then $$m^{(-2)}$$ is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9
Math Expert
Joined: 02 Sep 2009
Posts: 65785
If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

20 Dec 2012, 06:25
5
4
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

$$m^{-1} = -\frac{1}{3}$$;

$$\frac{1}{m}=-\frac{1}{3}$$;

$$m=-3$$.

$$m^{-2}=\frac{1}{m^2}=\frac{1}{9}$$.

_________________
GMAT Club Legend
Joined: 11 Sep 2015
Posts: 4987
GMAT 1: 770 Q49 V46
If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

Updated on: 12 Nov 2019, 17:21
4
Top Contributor
If mˉ¹ = -1/3 then mˉ² is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

Some good solutions here.
Here's one more approach:

CONCEPT: b^(-n) = 1/(b^n)

Given: mˉ¹ = -1/3
Rewrite as: 1/m = 1/(-3)
We can see that m = -3

So, mˉ² = 1/(m²) = 1/(-3)² = 1/9

_________________
If you enjoy my solutions, you'll love my GMAT prep course.

Originally posted by BrentGMATPrepNow on 27 Jul 2016, 06:53.
Last edited by BrentGMATPrepNow on 12 Nov 2019, 17:21, edited 1 time in total.
SVP
Status: The Best Or Nothing
Joined: 27 Dec 2012
Posts: 1705
Location: India
Concentration: General Management, Technology
WE: Information Technology (Computer Software)
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

27 Feb 2014, 19:20
4
2
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

$$\frac{1}{m} = \frac{-1}{3}$$

Squaring both sides

$$\frac{1}{m^2} = \frac{1}{9} =$$Answer = D
##### General Discussion
Target Test Prep Representative
Affiliations: Target Test Prep
Joined: 04 Mar 2011
Posts: 2800
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

28 Jun 2016, 04:48
If m^(-1) = -1/3 then m^(-2) is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

Since we know that m^-1 = -1/3 and m^-2 = (m^-1)^2, then m^-2 = (-1/3)^2 = 1/9.

_________________

# Jeffrey Miller | Head of GMAT Instruction | Jeff@TargetTestPrep.com

250 REVIEWS

5-STAR RATED ONLINE GMAT QUANT SELF STUDY COURSE

NOW WITH GMAT VERBAL (BETA)

See why Target Test Prep is the top rated GMAT quant course on GMAT Club. Read Our Reviews

Current Student
Joined: 12 Aug 2015
Posts: 2516
Schools: Boston U '20 (M)
GRE 1: Q169 V154
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

29 Jul 2016, 10:52
M^-1=-1/3=> M=-3
hence M^-2=1/9
Smash D
_________________
Intern
Joined: 12 Jun 2016
Posts: 26
Location: India
Concentration: Entrepreneurship, Finance
GPA: 3.76
WE: Information Technology (Computer Software)
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

29 Jul 2016, 11:14
1
m^(-1) = -(1/3)
Squaring both sides
m^(-2) = 1/9

Ans. D
Intern
Joined: 26 Sep 2016
Posts: 5
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

27 Sep 2016, 13:26
$$m^-1 = \frac{-1}{3}$$

$$\frac{1}{m} = \frac{-1}{3}$$

By cross multiplication

$$-m = 3$$

Squaring both sides

$$m^2 = 9$$

So $$m^-2 = \frac{1}{9}$$
Senior Manager
Joined: 14 Oct 2019
Posts: 406
Location: India
GPA: 4
WE: Engineering (Energy and Utilities)
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

19 Apr 2020, 07:12
m^(−1)=−1/3
now,squaring both sides
[m^(−1)]^2=[−1/3]^2
m^(−2)=1/9.

Intern
Joined: 02 Mar 2020
Posts: 49
Re: If m^(-1) = -1/3 then m^(-2) is equal to  [#permalink]

### Show Tags

20 Apr 2020, 07:11
If $$m^{(-1)} = -\frac{1}{3}$$ then $$m^{(-2)}$$ is equal to

(A) -9
(B) -3
(C) -1/9
(D) 1/9
(E) 9

Pretty simple and straight forward, doesn't really require any calculations.
Base raised to negative exponent = $$\frac{1}{m} = -\frac{1}{3}$$ Thus $$\frac{1}{m^2} = (-\frac{1}{3})^2 = \frac{1}{9}$$
Non-Human User
Joined: 09 Sep 2013
Posts: 15597
Re: If m−1=13, then m−2  [#permalink]

### Show Tags

26 Apr 2020, 03:12
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Re: If m−1=13, then m−2   [#permalink] 26 Apr 2020, 03:12